2008
DOI: 10.1016/j.vaccine.2008.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of live vaccine virus, comparative safety, and influenza-specific antibody responses after administration of live attenuated and inactivated trivalent influenza vaccines to HIV-infected children

Abstract: HIV-infected children (n = 243), ≥5 to <18 years old, receiving stable antiretroviral therapy, were stratified by immunologic status and randomly assigned to receive intranasal live attenuated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 37 publications
3
45
0
3
Order By: Relevance
“…This vaccine has been well tolerated and immunogenic in previously immunized HIV-infected children and adults, but its efficacy in this population has not been established. [3][4][5] LAIV is more effective than TIV in healthy children and confers protection against infection with mismatched strains ofinfluenza. 6,7 Serum antibody responses to LAIV, unlike those to TIV, do not correlate with protection against wild-type infection and the mechanism(s) of protection by LAIV is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…This vaccine has been well tolerated and immunogenic in previously immunized HIV-infected children and adults, but its efficacy in this population has not been established. [3][4][5] LAIV is more effective than TIV in healthy children and confers protection against infection with mismatched strains ofinfluenza. 6,7 Serum antibody responses to LAIV, unlike those to TIV, do not correlate with protection against wild-type infection and the mechanism(s) of protection by LAIV is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…herpes zoster vaccination, in RA patients receiving immunotherapies has to be clarified [7]. Certainly of interest are immunogenicity and safety aspects of live-attenuated nasal influenza vaccines in immuncompromised RA patients, but have been so far only investigated in children with cancer [70,71] and HIVinfected patients [72].…”
Section: Resultsmentioning
confidence: 99%
“…A study of 57 HIV-infected adults vaccinated with LAIV found no adverse safety concerns and did not demonstrate prolonged viral shedding; 23 similar findings were seen in studies of HIV-infected children. 24,25 However, since data on LAIV have been limited, guidelines continue to recommend against its use. HIV patients with mild egg allergies (only hives without other allergic symptoms) may receive IIV per the guidelines, and a vaccine is now available for those with more severe forms of egg allergy (RIV3, Flublok).…”
Section: Inactivated (Non-live) Vaccinesmentioning
confidence: 99%